Orientación en el posgrado - Batlle, Silvia; Alberto, Carolina; Barletta, César Martín; Pacheco, Emmanuel; Parodi, Silvana; Sansone, Cristina; Sulca, Susana (2017)
En los últimos años se ha producido un incremento de la oferta de posgrados, de alumnos inscriptos, carreras y modalidades de dictado. Todos estos fenómenos han traído una modificación en el tipo de trayectoria personal, educativa y laboral de los profesionales y una demanda a la Orientación de información actualizada para la creación de modelos teóricos y de intervención en esta área. En este trabajo se analizará la motivación de la elección del posgrado y de la modalidad de cursado. La estrategia teórica es psicosocial y la aproximación metodológica es cualitativa. Se acercan algunas ideas para la intervención en el Posgrado.
In the last years there has been an increase in the post graduate courses offer, the number of enrolled students, offered degrees and teaching modes. All this phenomena have brought a modification in the type of personal, educational and work trajectories for professionals and an updated demand for information to Orientation, for the creation of theoretical and intervention models in this area. This work analyzes the motivation for choosing a post graduate course and the learning mode. The theoretical strategy is psychosocial and the methodological approach is qualitative. Some ideas for post graduate courses intervention are approached.